Protective role of yeast beta-glucan on lead acetate-induced hepatic and reproductive toxicity in rats - Seven, Pinar Tatli; Mutlu, Seda Iflazoglu; Seven, Ismail; Arkali, Gozde; Kaya, Seyma Ozer; Kanmaz, Osman Ersin (Springer Heidelberg, 2021)
Lead (Pb) is one of the most common environmental pollutants and causes adverse effects on human and animal health. This study aimed to evaluate the protective role of beta-glucan against hepatic and reproductive toxicity induced by lead acetate. A total of 28 Sprague Dawley male rats were distributed into four groups (n = 7). The control group was intraperitoneally injected saline (1 ml/kg b.w.) daily for 21 days, the Pb group was intraperitoneally injected lead acetate (15 mg/kg b.w.) daily for 21 days, the beta-glucan group was orally administrated beta-glucan (50 mg/kg b.w.) daily for 21 days, and the Pb + beta-glucan group was intraperitoneally injected lead acetate (15 mg/kg b.w.) daily following the oral administration of beta-glucan (50 mg/kg b.w.) daily for 21 days. Results showed that feed intake in the Pb + beta-glucan group was significantly increased in comparison with that of the Pb group (p < 0.001). We also found that liver malondialdehyde (MDA) level was increased significantly in the Pb group (p < 0.01), while glutathione (GSH) level (p < 0.05), glutathione peroxidase (GSH-Px) (p < 0.05), and catalase (CAT) (p < 0.01) activities were reduced when they were compared with control. Moreover, Pb administration increased expression of pro-apoptotic protein Bax, the ratio of Bax/Bcl-2, and decreased the expression of the antiapoptotic protein Bcl-2 (p < 0.01). Also, Pb was found to cause a significant decrease in sperm motility (p < 0.01) and sperm concentration (p < 0.05) but increase in sperm tails and total sperm anomalies (p < 0.05). These findings were partially preserved by the administration of beta-glucan. Taken together, these results indicated that beta-glucan has the potential to alleviate the Pb-induced toxicity.
Keywords: Beta-glucan; Lead toxicity; Feed intake; Body weight change; Oxidative stress; Apoptosis; Sperm; Testis